Conception and design of high‐performance steel‐concrete composite slabs. Issue 2 (1st September 2021) - Pereira, Miguel; Simões, Rui; Craveiro, Hélder
Abstract: The main advantages of steel‐concrete composites slabs are the speed of construction, the elimination of conventional shuttering and the reduction of props. This structural system is widely used, mainly in the execution of floors in composite buildings. Usually, the longitudinal shear resistance is commonly provided by the embossments along the steel sheet. This paper presents an innovative reinforcing system that increases the longitudinal shear capacity and consequently the structural performance of composite slabs. The system is constituted by a set of transversal reinforcement crossing the steel sheeting which allows to take more advantage of the high bending resistance of composite slabs and increase their ductility. Two experimental campaigns were carried out: a small‐scale test programme, to study the resistance provided by the reinforcing system, and a full‐scale test programme, to assess the efficacy of the proposed reinforcing system. The present study allowed to conclude that the resistance and the ductility of composite slabs using the proposed reinforcing system are significantly increased. The design methodology based on the partial connection method can be used to predict the resistance of a composite slab incorporating the proposed reinforcing system.